WORKSHOP PERSONAL DEVELOPMENT DALAM PENINGKATAN KEPERCAYAAN DIRI BERKOMUNIKASI PADA ANAK BINAAN YAYASAN INSAN SAPA DHUAFA: Personality Development Training In Increasing The Self-Confidence Of Communication In Children In Sapa Dhuafa Research Children's Foundation - Pramelani; RR Roosita Cindrakasih; Taqwa Sejati; Muhamad Jejen Jaelani (Pakis Journal Institute, 2023)
the children assisted by the Insan Sapa Dhuafa Foundation which trains self-confidence focused on communication practices. Children never get insight into personal development in communication. Therefore, with the conditions experienced by the partners, this community service activity has the theme